Medical Conditions that Could Affect Oral Health Care Among Children Living in Governmental Orphanage Centers: A Case-Control Study - Bagher, Sara; Alamoudi, Rana; Trad, Rewaa; Shaker, Raneem; Alamoudi, Reham; Bader, Rayan; Sabbagh, Heba (Journal of King Abdulaziz University: Medical Sciences, 2023)
The study aimed to assess the medical health conditions that could affect oral health care among children living in governmental orphanage centers compared to non-orphan children living with their parents. This case-control study included 6- to-12-year children living in five-governmental orphanages (cases) that are matched in gender and age with children living with their parents (controls) in Jeddah, Saudi Arabia. At the scheduled appointment, a trained dentist interviewed the caregiver through a validated Arabic questionnaire consisting of the Socio-demographic information of the child and guardian and the medical history of the children. A total of 70 children in the case group and 155 in the control group were included with a mean age of 7.47±2.26. Significantly more children living in governmental orphanage centers were diagnosed with medical problems that might affect their dental health, including congenital heart disease (P=0.029) and mental/cognitive/psychologic and behavioral disorders (P=0.005). Children living in governmental orphanage centers are more likely than children who live with their parents to be affected by medical conditions that might impact their dental health care, which calls for special dental care precautions for this population.